Searching for bacterial plastitrophs in modified Winogradsky columns - Olabemiwo, Fatai A.; Kunney, Claudia; Hsu, Rachel; De Palo, Chloe; Bashaw, Thaddeus; Kraut, Kendall; Ryan, Savannah; Huang, Yuting; Wallentine, Will; Kalra, Siddhant; Nazzaro, Valerie; Cohan, Frederick M. (Frontiers in Microbiomes, 2024)
Plastic pollution has surged due to increased human consumption and disposal of plastic products.Microbial communities capable of utilizing plastic as a carbon source may play a crucial role in degrading and consuming environmental plastic. In this study, we investigated the potential of a modified Winogradsky column (WC) to enrich Connecticut landfill soil for plastic-degrading bacteria and genes.By filling the columns with the landfill soil and inorganic Bushnell Haas medium, and incorporating polyethylene (PE) strips at different soil layers, we aimed to identify bacterial taxa capable of degrading PE. After 12 months of incubation, distinct colors were observed along the WC layers, indicating successful cultivation. We employed high-throughput 16S rRNA sequencing to identify the microbes cultivated on the plastic strips and the intervening landfill soil. Sequencing revealed significant differences in bacterial communities between the two habitats, including increased abundance of the phyla Verrucomicrobiota and Pseudomonadota (née Proteobacteria) on the strips. We then used PICRUSt2 to estimate the functional attributes of each community from 16S rRNA sequences. Based on inferred genomic content, the most highly abundant proteins in PE strip communities tended to be associated with plastic degradation pathways. Phylogenetic analysis of 16S rRNA sequences showed novel unclassified phyla and genera enriched on the plastic strips. Our findings suggest PE-supplemented Winogradsky columns can enrich for plastic-degrading microbes, offering insights into bioremediation strategies.